Opioids, microglia, and temporal lobe epilepsy - Lankhuijzen, Lauren Marijke; Ridler, Thomas (Frontiers in Neurology, 2024)
A lack of treatment options for temporal lobe epilepsy (TLE) demands an urgent quest for new therapies to recover neuronal damage and reduce seizures, potentially interrupting the neurotoxic cascades that fuel hyper-excitability. Endogenous opioids, along with their respective receptors, particularly dynorphin and kappa-opioid-receptor, present as attractive candidates for controlling neuronal excitability and therapeutics in epilepsy. We perform a critical review of the literature to evaluate the role of opioids in modulating microglial function and morphology in epilepsy. We find that, in accordance with anticonvulsant effects, acute opioid receptor activation has unique abilities to modulate microglial activation through toll-like 4 receptors, regulating downstream secretion of cytokines. Abnormal activation of microglia is a dominant feature of neuroinflammation, and inflammatory cytokines are found to aggravate TLE, inspiring the challenge to alter microglial activation by opioids to suppress seizures. We further evaluate how opioids can modulate microglial activation in epilepsy to enhance neuroprotection and reduce seizures. With controlled application, opioids may interrupt inflammatory cycles in epilepsy, to protect neuronal function and reduce seizures. Research on opioid-microglia interactions has important implications for epilepsy and healthcare approaches. However, preclinical research on opioid modulation of microglia supports a new therapeutic pathway for TLE.